The effects of different temperatures and pH levels on growth rate and survival of juvenile Pomacea canaliculata in controlled environment / Marie Urai Clement - Clement, Marie Urai (2022)
Invasive apple snail, Pomacea canaliculata is one of the major pests that affected the production of rice in Malaysia. With the unpredictable changes on global climatic in Malaysia, it is important to have knowledge on the effect of water temperature and pH on growth and survival rate of P. canaliculata in water body, in order to avoid loss in paddy field and its adversely affect to the ecosystem. Water temperature and pH are parts of the most important environmental factors influencing the survival, growth rate, reproduction and behaviour of freshwater snails. This study is focused on the juvenile P. canaliculata due to scarce research study of juvenile snail. Moreover, this study can be served as foundation knowledge of P. canaliculata in Malaysia. The aim of this study is to evaluate the growth and survival rate of juvenile P. canaliculata at different temperatures and pH levels. The experiment was planned in a Randomized Complete Block Design (RCBD). 10 replications were assigned for each treatment. Growth and survival of juvenile P. canaliculata were evaluated at different constant water temperatures (15, 20, 25, 30 and 35°C). The findings show, at 30° C the growth rate of P. canaliculata is higher compare with the other temperature, however with low survival rate. Meanwhile, at room temperature (21 - 24°C), higher survival rate (100%) is recorded. For pH water level, growth and survival rate of juvenile P. canaliculata were also evaluated at different pH levels (4-4.9, 5-5.9, 6-6.9 and 7-7.9 pH). The results showed significant different of 4-4.9 pH from other treatments, p<0.05. The juvenile P. canaliculata in treatment 4-4.9 showed the lowest growth and survival rate while, the highest showed at pH level 6-6.9. The results showed that different water temperatures and pH levels affect the growth and survival rate of P. canaliculata and it is an important indicator for predicting and understanding the changes of water temperature when controlling this pest.